Identification of microorganisms responsible for spoilage of tomato (Lycopersicon esculentum) fruit - Ghosh, Abhinaba (Journal of Phytology, 2009)
Tomato contains large amount of water which makes them more susceptible to spoilage by the action of various microorganisms. This makes the storage of this vegetable difficult and its transportation too. Tomato is a prevalent vegetable used both in raw form as salad, for garnishing various food items and added for taste in various cooked items. Thus it forms a major ingredient of food both in Asia as well as European countries. Further tomato is rich source of vitamins especially Vitamin A as it contains its precursor ÃŽÂ²-carotene which is very essential for vision. It is also a rich source of minerals which makes it an essential component of food. This study was done to find out the organisms which make tomato more susceptible to spoilage. Out of the 30 Rose Bengal agar plates which were inoculated and incubated vigorous growth of fungi was observed in 26 plates with moderate growth on other 4 plates. Also 30 other plates of Nutrient agar were inoculated with the sample and very scanty growth of bacterial colonies was observed in 3-4 plates and mostly occupied by fungal colonies. Thus it was found that fungi were the source of spoilage in most of the samples rather than bacteria. Further morphological studies were done to know the fungal member responsible for the spoilage. Among the fungi, it was found that Aspergillus niger and Fusarium were found in most of the spoiled samples with a few samples containing Penicillium too with A. niger dominating all the plates. Since all these are fungi, it can be related to the severity of the intake of spoiled tomato are developing countries like India where people hardly discard the spoiled foods as spores are relatively heat-resistant and do not perish and spread easily. Also the outcome can be dangerous since these fungi are the source of highly potent mycotoxins which can cause severe food poisoning resulting in fatal outcome.